Understanding development and proficiency in writing quantitative corpus linguistic approaches - Durrant, Philip 1976-; Brenchley, Mark 1981-; McCallum, Lee 1989- (Cambridge University Press, 2021)
Quantitative corpus research on written language development has expanded rapidly in recent years, assisted by the ever-increasing power and accessibility of software capable of reliably analysing huge collections of learner writing. For this work to reach its full potential, it is important that researchers have a strong understanding of its methodological foundations and of the existing empirical evidence base on which it can build. This book provides the most comprehensive discussion to date of research in this area. Covering both first and second language learning contexts, it sets out a coherent theoretical framework and systematically reviews studies published over the last seventy years in order to establish what such research has taught us about written language development, what it hasn't taught us, and what we should do next. Timely and original, this is an essential reference work for academic researchers and students of first and second language writing
Title from publisher's bibliographic system (viewed on 22 Feb 2021)
Keywords: English language / Rhetoric / Study and teaching / Evaluation; English language / Study and teaching / Evaluation; Corpora (Linguistics); Computational linguistics